Recycled Concretes Made with Waste Ready-Mix Concrete as Coarse Aggregate - Zega, Claudio Javier (2011)
Using waste materials for new products is a global trend undergoing rapid development. Recycling materials allows for a more efficient life cycle and contributes to environmental protection. In the construction field, this trend has gained importance because of the shortage of natural resources and because of environmental problems caused by storing building-demolition wastes. This situation has led to the search for new applications for these wastes, and their use as aggregates in concrete is an interesting alternative. In this paper, some characteristics of recycled coarse aggregates obtained by crushing waste ready-mix concrete, as well as the mechanical and durability properties of recycled concretes made by using 25, 50, and 75% of these aggregates, are presented. Recycled concretes show lower compressive strength than conventional concrete for the higher strength level, whereas the durability properties of the two are similar.